High Risk? Indoor Cannabis Producers' Perceptions of Occupational Health and Safety. Issue 4 (2nd October 2021) - Trask, Catherine; Koehncke, Niels; Trask, David
ABSTRACT: Introduction : Recent legal changes mean Canadian cannabis production has moved from an illegally grown crop to a potentially common one. However, little is known about the needs of long-time producers accustomed to operating outside a legal framework. In order to develop effective safety communication strategies, there is a need to better understand cannabis producers' perceptions of OHS regulations, OHS controls, and sources of OHS information. Methods : The specific objectives of this study are to (1) Describe production tasks and identify potential hazards related to these tasks and (2) describe workers' current sources of OHS information. This study gathered two types of information: facility and production information gathered from key informants during three facility walkthroughs, and health and safety perceptions gathered during face to face interviews with nine cannabis production workers. Interviews were thematically analyzed using interpretive description. Results : Cannabis production and related occupational health and safety issues occur within a larger context, and descriptions of contextual factors were interwoven with workers' responses which, on the whole, expressed positive views of occupational health and safety. Perceived barriers to OHS included cost, lack of specialized skills, and lack of worker consultation, while named sources of OHS information included courses, requests to OHS agencies, and the internet. Conclusion : It is hoped that an enhanced understanding of Canadian cannabis producers can inform the development of effective occupational health and safety interventions to promote the health and productivity in this workforce.